Open-label use of Anakinra (Kineret) in the treatment of patients with osteoarthritis - Craig Davis Scoville; John Partridge Dickson (Indian Journal of Rheumatology)
Background: Novel treatments for osteoarthritis (OA) are needed for patients not responding to and/or not tolerating conventional treatments. In this prospective study the usefulness of Anakinra (Kineret) in the treatment of OA was evaluated. Methods: Eleven patients with symptomatic OA were treated with Anakinra (Kineret) over a 2–3 month period. Efficacy of response was determined if patients showed >30% improvement in the Western Ontario and McMaster Universities Osteoarthritis Index and/or Australian/Canadian Osteoarthritis Hand Index scoring with treatment. Nine of the 11 patients received Kineret intra-articular (IA) injections and 2/11 patients with erosive polyosteoarthritis received Kineret 100 mg subcutaneous injections daily for 30 days. Results: One of the two patients receiving systemic administration of Kineret showed mild efficacy. A total of 21 IA Kineret injections were performed on nine patients. Only 2/5 patients receiving IA Kineret injections into small/medium-sized joints showed efficacy and only 2/5 patients receiving IA Kineret injections into large joints (knees, shoulders) showed efficacy – but those patients showing efficacy with large joints injections had >50% improvement. Conclusion: In this study it was found that patients receiving large joint injections were more likely to show greater efficacy than those receiving small joint injections. Therefore, there seems to be a possible benefit of using Kineret (150–200 mg) in the treatment of OA in large joints and may represent an alternative to IA steroid in those patients in whom steroids may be contraindicated.